Two-Way Continual Authentication Model - Lugani, Carlos Fabián (2017)
Authentication is a process by which a person using a personal computer, information system or device, defines its identity, and therefore, such system grant access based on predefined permissions. The use of biometric devices, IoT devices, wearable technology and other similar devices, define present authentication methods as weak and requires a level of mutual authentication so that both actors trust each other granting who they claim or seem to be. This paper addresses that information systems and/or devices that should validate their identity in the same way users do. Additionally, due to the increasing information security incidents, there is a risk that one of the actors, during the connection process, might be an impostor instead of a truly actor. For this reason, the authentication method should be a continuous and ongoing process in order to counteract with the security risks mentioned above.